중년기 여성 당뇨병 환자의 자기관리 - 송자경; Ja Kyung Song; 최정숙; Jung Sook Choi; 정춘희; Choon Hee Chung; 장수미; Su Mi Jang; 김연수; Yoen Soo Kim (당뇨병(JKD), 2002)
Background: The purpose of this study was to evaluate the perceived level of empowerment of self management in middle aged women with diabetes in order to develop a self management of empowerment education program for diabetes. Method: To study self management of empowerment for diabetes, we classified four concepts such as self efficacy, social support, problem solving and recognized responsibility, which were the components of empowerment. The subjects were 37 middle aged (40~60) women with diabetes who came to be treated their diseases at the endocrinology out patient clinic in a medical center at Wonju City. Results: This study found a low level of empowerment of self management in middle aged women with diabetes. The mean scores for empowerment of self management were 2.81. The sub-concept of empowerment for self efficacy was 2.93, social support, 2.54, problem solving, 2.56, and recognized responsibility of self management, 3.22(1.0: usually not, 2.0: sometimes not, 3.0: sometimes, 4.0: usually). Generally, the results suggest that middle aged women with diabetes have the moderate level of empowerment in self management. Patients with diabetes recognize the responsibility of self control in diabetes, but have difficulties and stresses in managing diabetes. The patients with diabetes presented psycho-social needs which are real programs needed for treating their diabetes such as stress s management, psychological difficulties, and family support, etc. Conclusion: It is needed to develop the education programs and intervention strategies to enhance self efficacy, structure family and social support, exercise problem solving for middle aged women with diabetes and obtain subjective responsibility in the performance of self management with diabetes.